Prevalence and factors associated with body dysmorphic disorder in women under dermatological care at a Brazilian public institution - Morita, Mariana Mathias [UNESP]; Merlotto, Maira Renata [UNESP]; Dantas, Cassia Lopes [UNESP]; Olivetti, Fernando Henrique [UNESP]; Miot, Helio Amante [UNESP] (Elsevier B.V., 2021)
Background: Body dysmorphic disorder consists of excessive concern with minimal appearance defects, which causes functional impairment. Its prevalence is estimated to range from 5% to 35% of dermatological patients, especially adult women with esthetic complaints. Objectives: To investigate the prevalence and factors associated with dysmorphic disorder in female dermatological patients, in a public institution in Brazil. Methods: This was a cross-sectional study involving adult women attended at a public dermatological service in Brazil. Participants underwent a demographic survey, in addition to a screening form for body dysmorphic disorder (Body Dysmorphic Disorder Examination [BDDE]). The presence of dysmorphic disorder (BDDE > 66 points) was assessed among the participants according to demographic covariates and psychological problems, through logistic regression. Results: A total of 223 women were evaluated. The BDDE showed high internal consistency (Cronbach's alpha =0.90). it is noteworthy the high prevalence of psychological problems and the fact that over one-third (38%) of the sample presented a high degree of dissatisfaction with their image. The prevalence of dysmorphic disorder was 48% among women with esthetic complaints and 30% among the others (p < 0.01). Lower family income (OR = 2.97), history of domestic violence (OR =3.23), search for dermatological care due to an esthetic complaint (OR = 2.05), and suicidal ideation (OR = 4.22) were independently associated with the occurrence of body dysmorphic disorder. Study limitations: This was a single-center study of a non-randomized sample from public service. Conclusions: Body dysmorphic disorder is prevalent among female dermatological patients; it is associated with traumatic psychological experiences, tower income, affective disorders, and demand for esthetic care. It is essential to recognize the diagnosis in order to treat such patients and refer them for appropriate psychiatric treatment instead of trying to satisfy their esthetic demands. (C) 2021 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Alcoholism; Body image; Child abuse, sexual; Depression; Health surveys